Efektivitas Pendistribusian Zakat Oleh Badan Amil Zakat Nasional Kabupaten Siak : Studi Kecamatan Koto Gasib - Kartius; Herman Herman; Dedi Purnomo (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2022)
The National Amil Zakat Agency (Baznas) of Siak Regency is a zakat management agency in the Siak Regency area which is responsible for reports to the Regent. The purpose of this study was to analyze and explain the effectiveness of the distribution of Zakat by the National Amil Zakat Agency of Siak Regency (Koto Gasib District Study). The type of research used is descriptive research with qualitative methods by analyzing data in the form of interviews and observations. The study was conducted in Koto Gaasib District, Siak Regency by assessing the effectiveness of the distribution of zakat carried out by Baznas, Siak Regency, to Mustahik in Koto Gasib District. The sample in this study consisted of the Head of Baznas, Deputy II for Distribution and Utilization, staff, UPZ Koto Gasib and Mustahik. The results of the research conducted have not been fully effective because there are still several obstacles found, including the socialization carried out by Baznas has not been maximized because the purpose of socialization is focused on muzakki. In addition, reporting from mustahik regarding its business development is also not clear. The suggestions that will be recommended are that the socialization must be balanced to both muzakki and mustahik, as well as the reporting provided by mustahik about business development to the Baznas of Siak Regency.